Analysis of the Accident Rate of the Constituent Entities of the Russian Federation - Shevtsova A. G. (EDP Sciences, 2021)
Every year, tens of thousands of road traffic accidents occur on the territory of Russia, characterized by different accident rates. Some of the most common are road traffic accidents, in the place of which violations of the mandatory requirements for the operational state of highways and railway crossings have been recorded under the conditions of ensuring road safety. The condition of the asphalt concrete road surface affects the grip performance of the vehicle with the road. It is necessary to study the statistics of road traffic accidents in the constituent entities of the Russian Federation located in different road and climatic zones in order to determine the dependence and the degree of influence of the state of the road surface on the number of accidents occurring.